f(x) = x^3+2x^2-x-2 . Solve for f(x) = 0

f(x) = x3 + 2x2 - x - 2 Use the factor theorem to test for f(1) = 0 f(1) = 13 + 2*12 - 1 - 2 = 0 Therefore x = 1 is a solution and (x-1) is a factor of f(x) Now factorise f(x) x3 + 2x2 - x - 2 = (x-1)(x2 + 3x + 2) = (x-1)(x+2)(x+1) So x = 1, -2, -1.

Answered by Elena S. Maths tutor

4056 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

how can differentiate using the product and chain rule? e.g y=(4x+1)^3(sin2x), find dy/dx.


The line L has equation 7x - 2y + 11 = 0, Find the gradient of l


A curve C has equation y = (2 - x)(1 + x) + 3 . A line passes through the point (2, 3) and the point on C with x-coordinate 2 + h . Find the gradient of the line, giving your answer in its simplest form.


Given the equation 0=5x^2+3xy-y^3 find the value of dy/dx at the point (-2,2)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences